2012
DOI: 10.1002/pmic.201100418
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics reveals selective regulation of proteins in response to memory‐related serotonin stimulation in Aplysia californica ganglia

Abstract: The marine mollusk Aplysia californica (Aplysia) is a powerful model for learning and memory due to its minimalistic nervous system. Key proteins, identified to be regulated by the neurotransmitter serotonin in Aplysia, have been successfully translated to mammalian models of learning and memory. Based upon a recently published large-scale analysis of Aplysia proteomic data, the current study investigated the regulation of protein levels 24 and 48 h after treatment with serotonin in Aplysia ganglia using a 2-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…These graphs show the most-represented terms across gene ontology levels (multilevel); the numbers in parenthesis represent a scoring/weighting system used by Blast2Go (Conesa et al 2005) to weight the representation of gene ontology terms. The complexity of response we observed here was not captured in previous proteomic screens, which identified only a handful of changes in protein expression 1 d after LTS training (Castellucci et al 1988) or serotonin exposure (Barzilai et al 1989;Monje et al 2012). It is possible that the transcriptional changes we observed do not always yield alterations in protein expression.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These graphs show the most-represented terms across gene ontology levels (multilevel); the numbers in parenthesis represent a scoring/weighting system used by Blast2Go (Conesa et al 2005) to weight the representation of gene ontology terms. The complexity of response we observed here was not captured in previous proteomic screens, which identified only a handful of changes in protein expression 1 d after LTS training (Castellucci et al 1988) or serotonin exposure (Barzilai et al 1989;Monje et al 2012). It is possible that the transcriptional changes we observed do not always yield alterations in protein expression.…”
Section: Discussionmentioning
confidence: 62%
“…Despite this, there is a strong concor-dance between our results and these previous screens. For example, our list overlaps with at least 5 of the 19 proteins identified by Monje et al (2012): calponin, calreticulin, glutathione S-transferase, a heterogeneous nuclear riboprotein, and tubulin. 1 Monje et al (2012) identified regulated proteins with the accession number of the closest matching protein in any species making precise matching to Aplysia transcripts somewhat provisional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already explored memory processes through the prism of proteomics. Both invertebrate (Crow & Xue‐Bian, ; Monje et al ., ) and vertebrate models (Henninger et al ., ; Li et al ., ; Monopoli et al ., ; Kähne et al ., ; Hong et al ., ; Rao‐Ruiz et al ., ; Smidak et al ., ) were investigated. Smidak et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many others have examined changes in transcription or protein expression at different time points after 5-HT exposure in whole animals, ganglia, or cultured neurons (e.g. Barzilai, Kennedy, Sweatt, & Kandel, 1989; Monje et al, 2011). In a previous analysis of a small set of transcripts, however, we have shown that 5-HT and behavioral training do not always produce similar patterns of transcriptional change in Aplysia californica (Bonnick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%